Learning environment, attitudes and anxiety across the transition from primary to secondary school mathematics - Deieso, D.; Fraser, Barry (Springer, 2018)
Past research has revealed that, relative to primary-school students, high-school students have less-positive attitudes to mathematics and perceive their classroom environments and teacher–student relationships less favourably. This study involved the transition experience of 541 students in 47 classes in 15 primary (year 7) and secondary (year 8) government and Catholic schools in metropolitan and regional South Australia. Scales were adapted from three established instruments, namely, the What Is Happening In this Class?, Test of Mathematics Related Attitudes and Revised Mathematics Anxiety Ratings Scale, to identify changes across the transition from primary to secondary school in terms of the classroom learning environment and students’ attitude/anxiety towards mathematics. Relative to year 7 students, year 8 students reported less Involvement, less positive Attitude to Mathematical Inquiry, less Enjoyment of Mathematics and greater Mathematics Anxiety. Differences between students in Years 7 and 8 were very similar for male and female students, although the magnitude of sex differences in attitudes was slightly different in Years 7 and 8.